Functional Role of the Prokaryotic Proline-tRNA Synthetase Insertion Domain in Amino Acid Editing - Wong, Fai-Chu; Beuning, Penny J; Nagan, Maria; Shiba, Kiyotaka; Musier-Forsyth, Karin (Biochemistry (Easton), 2002)
Aminoacyl-tRNA synthetases catalyze the attachment of specific amino acids to cognate tRNAs in a two-step process that is critical for the faithful translation of genetic information. During the first chemical step of tRNA aminoacylation, noncognate amino acids that are smaller than or isosteric with the cognate substrate can be misactivated. Thus, to maintain high accuracy during protein translation, some synthetases have evolved an editing mechanism. Previously, we showed that class II Escherichia coli proline-tRNA synthetase (ProRS) is capable of (1) weakly misactivating Ala, (2) hydrolyzing the misactivated Ala-AMP in a reaction known as pretransfer editing, and (3) deacylating a mischarged Ala-tRNAPro variant via a post-transfer editing pathway. In contrast to most systems where an editing function has been established, pretransfer editing by E. coli ProRS occurs in a tRNA-independent fashion. However, neither the pre- nor the post-transfer editing active site(s) has been identified. Sequence analyses revealed that most prokaryotic ProRSs possess a large insertion domain (INS) between class II conserved motifs 2 and 3. The function of the ∼180-amino acid INS in E. coli ProRS is the subject of this investigation. Alignment-guided Ala scanning mutagenesis was carried out to test conserved amino acid residues present in the INS for their role in pre- and post-transfer editing. Our biochemical data and modeling studies suggest that the prokaryotic INS plays a critical role in editing and that this activity resides in a domain that is functionally and structurally distinct from the aminoacylation active site.